(untitled) (LACCEI, 2024)
The purpose of this research is to determine the relationship between digital marketing and customer relationship management in a cargo transport company Cajamarca S.A., the type of research is basic with a quantitative approach, the design is non-experimental, and whose level of research is correlational. And cross-sectional, the population and sample, were made up of 20 clients of the company The technique used in the investigation was the survey and the instrument that was applied was the online questionnaire, with a reliability according to Cronbach’s Alpha of 0.814 and was validated by expert judgment. Finally, it was demonstrated that the relationship between digital marketing and customer relationship management (CRM) of the company, is direct and positive, these results were verified through the Rho Spearman coefficient, obtaining a correlation of 0.765, it presents a bilateral significance level of 0.000, which is less than 0.05, therefore, the variables are related to each other and there is a very strong positive correlation, effectively demonstrating that when digital marketing is properly managed, good customer relationship management will be obtained. Customers of the company.